Drug repurposing for the treatment of alveolar echinococcosis: In vitro and in vivo effects of silica nanoparticles modified with dichlorophen - Fabbri, Julia (2019)
Alveolar echinococcosis is a neglected parasitic zoonosis caused by the metacestode Echinococcus multilocularis, which grows as a malignant tumour-like infection in the liver of humans. Albendazole (ABZ) is the antiparasitic drug of choice for the treatment of the disease. However, its effectiveness is low, due to its poor absorption from the gastro-intestinal tract. It is also parasitostatic and in some cases produces side-effects. Therefore, an alternative to the treatment of this severe human disease is necessary. In this context, the repositioning of drugs combined with nanotechnology to improve the bioavailability of drugs emerges as a useful, fast and inexpensive tool for the treatment of neglected diseases. The in vitro and in vivo efficacy of dichlorophen (DCP), an antiparasitic agent for intestinal parasites, and silica nanoparticles modified with DCP (NP-DCP) was evaluated against E. multilocularis larval stage. Both formulations showed a time and dose-dependent in vitro effect against protoscoleces. The NP-DCP had a greater in vitro efficacy than the drug alone or ABZ. In vivo studies demonstrated that the NP-DCP (4 mg kg-1) had similar efficacy to ABZ (25 mg kg-1) and greater activity than the free DCP. Therefore, the repurposing of DCP combined with silica nanoparticles could be an alternative for the treatment of echinococcosis.